Indonesian Propolis Inhibit Proinflammatory Cytokines, Apoptosis and Oxidative Stress in Anthrax Animal Model - Ratih Tri Kusuma Dewi; Dhani Redhono; Agung Susanto; Diding Heri Prasetyo; Evi Nurhayatun; Ida Nurwati; Bambang Purwanto (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Anthrax is a zoonotic disease caused by Bacillus anthracis, whose endospores stimulate the release of pro-inflammatory cytokines and promote oxidative stress. Propolis, a natural resource that can be found in Indonesia, has been proven to have anti-apoptotic and antioxidant role which might be a potential adjuvant therapy for anthrax treatment. Hence in this study we aimed to investigate effect of propolis as an anti-inflammatory, anti-apoptotic, and antioxidant in anthrax rats model by examining the level of tumor necrosis factor (TNF)-α, caspase-3, and malondialdehyde (MDA), respectively.METHODS: This was an experimental post-test only study with 40 male rats weighed 180-200 g that were induced by anthrax spores injected subcutaneously. The rats were divided into one control positive group and four intervention groups that were administered with 200 mg/kgBW propolis extract for 7 to 14 days. The levels of serum TNF-α, caspase-3, and MDA were measured using enzyme-linked immunosorbent assay (ELISA) and analyzed with bivariate analysis.RESULTS: TNF-α, caspase-3, and MDA level were found lower in anthrax rats model given ethanol extract of propolis than the control group. The lowest concentration of TNF-α value was found in group administered with propolis extract 200 mg/kgBW for 7 days before the anthrax induction (6.136±0.205 pg/mL). The results were similar to the MDA serum and caspase-3 which were the lowest when the propolis was administered 7 days earlier (1.893±0.188 nmol/mL and 2.040±0.067 ng/mL). There was significant difference in the TNF-α, caspase-3, and MDA serum levels (p≤0.001) compared to control group.CONCLUSION: Propolis has anti-apoptotic and antioxidant effects which can be used as complementary therapy in anthrax infection.KEYWORDS: propolis, anthrax, anti-apoptotic, antioxidants